Human dignity, speciesism, and the value of life - Grzegorz Hołub (Studia Ecologiae et Bioethicae)
This paper deals with a discussion concerning the value of life. Specifically, it addresses the idea of speciesism, a term coined by Peter Singer, whereby human life is endowed with special significance because of its membership in the species Homo sapiens. For Singer, it is an example of erroneous thinking. On such an account, the idea of human dignity seems to be highly problematic. In this article, the author directs a number of critical voices, both methodological and ontological, toward scepticism concerning a species belonging. He argues that natural species play quite important roles in the existing reality. The author further tries to prove that the realm of life should be associated with a so-called intrinsic value. In the light of that, any living entity possesses its axiological importance and should be considered and treated accordingly. Human dignity is a corollary of the special place accorded in such reasoning by the value of human life. The article concludes with a thesis that the stance arguing for human dignity is still unthreatened and ready for further development.